Tyrosol Suppresses Allergic Inflammation by Inhibiting the Activation of Phosphoinositide 3-Kinase in Mast Cells - Je, In-Gyu (PLoS One, 2015)
Allergic diseases such as atopic dermatitis, rhinitis, asthma, and anaphylaxis are attractive research areas. Tyrosol (2-(4-hydroxyphenyl)ethanol) is a polyphenolic compound with diverse biological activities. In this study, we investigated whether tyrosol has anti-allergic inflammatory effects. Ovalbumin-induced active systemic anaphylaxis and immunoglobulin E-mediated passive cutaneous anaphylaxis models were used for the immediate-type allergic responses. Oral administration of tyrosol reduced the allergic symptoms of hypothermia and pigmentation in both animal models. Mast cells that secrete allergic mediators are key regulators on allergic inflammation. Tyrosol dose-dependently decreased mast cell degranulation and expression of inflammatory cytokines. Intracellular calcium levels and activation of inhibitor of κB kinase (IKK) regulate cytokine expression and degranulation. Tyrosol blocked calcium influx and phosphorylation of the IKK complex. To define the molecular target for tyrosol, various signaling proteins involved in mast cell activation such as Lyn, Syk, phosphoinositide 3-kinase (PI3K), and Akt were examined. Our results showed that PI3K could be a molecular target for tyrosol in mast cells. Taken together, these findings indicated that tyrosol has anti-allergic inflammatory effects by inhibiting the degranulation of mast cells and expression of inflammatory cytokines; these effects are mediated via PI3K. Therefore, we expect tyrosol become a potential therapeutic candidate for allergic inflammatory disorders.